Shift duty and other sources of stress among nurses in the University College Hospital, Ibadan (2004)
This study was done to find out the various sources of stress among the nurses as well as the place of shift duty as a stress factor among the nurses at the University College Hospital (UCH), Ibadan. A cross- sectional study of one hundred and sixty-six nurses in the University College Hospital was done with the use of a self-administered questionnaire. The staff were selected from all the clinical departments by a stratified random sampling. The results show that shift duty was rated as the most important source of professional stress among the nurses, affecting 79 or 47.6% of the workers. The next two most important sources of occupational stress were poor wages and death of some patients. The commonest cause of non-(directly) occupational stress was problem with transportation - in 85 or 51.2% of the workers. Others were general poverty and children's illness. It is concluded that governments in Nigeria should pay attention to the sources of stress for the nurses. Better shift duty allowance should be paid to those who do so while the public transport system should be developed.